Effect of Price, Brand Image, and Product Quality on Customer Loyalty - Ade Perdana Siregar; Pandu Adi Cakranegara; Ovita Charolina; Gusti Noorlitaria Achmad; Teguh Setiawan Wibowo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the current era of globalization, many industries have developed rapidly and become industries that are able to provide consumer goods. However, with the development of the times, consumer needs are also increasing and varied. There are also many new companies that have been established and can also fulfill human needs. The human population is also increasing every day, so the need will also be endless. The purpose of this study is to analyze effect of price, brand image, and product quality on customer loyalty. The type of research used in this research is quantitative research. The population in this study are customers of PT Sarang Tawon Sukses Abadi totaling 75 respondents. The samples taken in this study are customers of PT Sarang Tawon Sukses Abadi totaling 75 respondents. Data analysis in the study of multiple linear regression analysis. The results show that price has a positive and insignificant effect on customer loyalty. Brand image has a positive and significant effect on customer loyalty. Brand image has a positive and significant effect on product quality.